The limitation of MFCA-based cost analysis for serial manufacturing process with sampling scheme - Wichai Chattinnawat (2018)
© IEOM Society International. This research aims to analyze the MFCA-based cost of a serial manufacturing process in which the incoming, inprocess and outgoing inspection are based on zero acceptance number sampling plan. Negative products generally occur along the serial production stages, not only in the forms of defectives but also in the form of wastes. Without 100% inspection, defectives from previous manufacturing stage can be escaped and sent to the next stage resulting in more loss and higher negative cost. In the case of serial process where defectives cannot be identified and withdrawn, the traditional calculation of MFCA cost may not be applied to identify the ineffectiveness of the process. Hence, the negative cost of material, system, energy and waste treatment cannot be allocated along the manufacturing streams or stages since the actual inherent defectives are unfolded. Hence, this presentation will propose solution how to analyze the MFCA cost structure for such serial manufacturing process gated with sampling inspection scheme. © IEOM Society International.